2011
DOI: 10.1248/cpb.59.1065
|View full text |Cite
|
Sign up to set email alerts
|

Four New Iridoid Glucosides from Ajuga reptans

Abstract: NoteAjuga reptans L. (Labiatae) is native to Europe, and has been used as a traditional vulnerary.1) This plant has been reported to contain iridoids, 1,2) diterpenoids, [3][4][5][6][7] ecdysteroids, [8][9][10] and anthocyanins.11) The present paper describes the isolation and structural elucidation of four new iridoid glucosides (1-4) along with four known iridoid glucosides (5-8), one known diterpenoid glycoside (9), one known aliphatic alcohol glycoside (10), and three known ecdysteroids (11-13), as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…In comparison with other research, A. laxmannii showed a higher antiradical capacity. For example, a study concerning antioxidant capacity of A. turkestanica reported a value of 57.84 ± 4.19 μg/mL ( Mamadalieva et al, 2013 ), whereas a similar study concerning A. reptans reported a slightly higher value (65.7 ± 3.82 μg/mL) ( Ono et al, 2011 ). A similar antiradical activity was reported by Movahhedin et al (2016) for A. chamaecistus subsp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with other research, A. laxmannii showed a higher antiradical capacity. For example, a study concerning antioxidant capacity of A. turkestanica reported a value of 57.84 ± 4.19 μg/mL ( Mamadalieva et al, 2013 ), whereas a similar study concerning A. reptans reported a slightly higher value (65.7 ± 3.82 μg/mL) ( Ono et al, 2011 ). A similar antiradical activity was reported by Movahhedin et al (2016) for A. chamaecistus subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several phytochemical studies on Ajuga species have shown the presence of iridoids, diterpenes, phytoecdy steroids, flavonoids, sterol glycosides and phenylethanoid glycosides as the main secondary metabolites of the genus ( Manguro et al, 2006 , 2011 ; Ono et al, 2011 ; Atay et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monoterpenoids ( 1 – 3 ) and polyphenols ( 4 – 7 ) are characteristic secondary metabolites of the Ajuga genus [ 11 , 12 ], exerting many health properties, having antioxidant, anti-inflammatory, and antibacterial effects [ 7 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The folk medicine attributes to A. reptans L. anti-diabetic, anti-hypertensive [ 9 ], diuretic [ 10 ], and hepatoprotective properties [ 11 ]. Ecdysteroids, triterpenes, sterols, diterpenes, iridoids, and flavonoids have been identified as bioactive compounds providing antioxidant power, antimicrobial, and anti-inflammatory activity [ 6 , 11 , 12 , 13 ]. Moreover, Ajuga extracts and the major phenylpropanoids were demonstrated as both antioxidant and UV protector agents in cosmetic formulations to counteract premature cell ageing [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ajuga reptans L. is frequently used in the traditional medicine of many countries especially, the eastern part of Europe, for its skin healing properties. The extracts obtained from "bugle" (Ajuga reptans L.) most likely own their activity to the content of polyphenols of the flavonoid and polyphenol-carboxylic acids type (antioxidant, vascular and antimicrobial properties), as well as of iridoids (anti-inflammatory and wound healing) [1]. Moreover, the research on cosmetic product for sun protection is evolving towards the development of natural products.…”
Section: Introductionmentioning
confidence: 99%